DEBUNKING BLACK STEREOTYPES THROUGH GRAY MATTER PLAY SCRIPT BY JEANETTE D. FARR (EUFONI: Journal of Language, Literary, and Cultural Studies, 2021)
Black stereotypes have emerged over centuries in The United States of America. A long history of slavery and injustice practices have constructed some images of those who are born black in that country. This study focuses on debunking black stereotypes in the play script entitled Gray Matter by Jeanette D. Farr. The qualitative approach is used in the discussion of this study; the main characterâ€˜s dialogues are analysed by using Judd and Park (1993) theory about stereotypes and Franzoi (2009) social psychology theory. The results of this study showed black   stereotypes   practices   towards   Afro-American including: â€˜black man is criminalâ€˜, â€˜black is dirtyâ€˜, and â€˜black comes from lower societyâ€˜. Eventually, the interpersonal relationship between the two characters is deepened and resulted on the debunking of all the stereotypes upon Russell.